New Student Admission Promotional Strategy Through Flagship Programs in an Effort to Increase Student Number at SD Kreatif Muhammadiyah Bangil - Alamsyah, Mardiana Anjani; Wurianto, Arif Budi; Tinus, Agus (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2025)
This study aims to describe the promotion strategy of New Student Admissions (PPDB) through flagship programs in an effort to increase student acquisition at SD Kreatif Muhammadiyah Bangil. The method used is descriptive qualitative research, with data obtained through interviews, observations and documentation. The results of the study show that the main flagship programs of 3T (Tajdid, Tahfidz, Tamyiz) are the main attractions. Promotions are carried out through social media, open tables and visits to partner schools. The evaluation of this promotion strategy showed an increase in the number of students by 13% compared to the previous year. The 3T flagship program is the dominant factor in the decision of students' parents to choose a school. However, challenges still arise in the form of public perception of private schools and limited promotional competence in some teachers. It is necessary to strengthen communication strategies and collaboration with local communities to increase the effectiveness of promotions.